Involvement Medical Students In Postpartum Depression (PPD) Educational Program Among Community In Koper Village - Komalasari, Rita; Siti Maulidya Sari; Adilah Rifat Hakimah; Dhea Putri Ardita; Helmi Fahmi Fauzi; Lucy; Laila Felicia; Raysha Damatri Rasyad (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pamulang, 2025)
The significant role of family members and community including cadres in identifying and supporting the mother with PPD. However, there is a lack of knowledge and awareness of the disorder. The aim is to increase knowledge and awareness of the cadres, women, and their families, community toward PPD by involving medical students in Koper Village. The educational program of PPD was conducted on 29 Desember 2022 in Koper District, Banten Province with the involvement of five medical students and 44 participants. The program included presentation, discussion, pre and post testing questionnaires. Data was analyzed using the SPSS 26 program. Wilcoxon signed rank test as a non-parametric test for un- distributed normal data was used. A significance value of 0.000 asymp.sig was obtained. (2-tailed < 0.05). This can be concluded that there is a significant increasing knowledge and awareness of PPD among participants toward PPD before and after the program. The involvement of medical students in the program has had a crucial impact on increasing the knowledge and awareness of the cadres, women, their families, and community . The sufficient knowledge of the participants could help them in identifying and supporting the mother, as well as the participants may also help other community members to raise awareness about PPD.